Ex vivo protocol for testing virus survival on human skin: experiments with herpesvirus 2. - Graham, M L (1996)
We report an ex vivo method, which uses pieces of human skin excised during routine plastic surgery, for testing survival of hazardous pathogens. Using this procedure, we compared the survival of human herpesvirus 2 on human skin and on metal disks. At the physiological skin temperature of 32 degrees C, the half-life of the virus on skin was 1.44 h while on metal disks it was 0.36 h. Even at ambient temperature (22 degrees C), the virus lost infectivity faster (half-life = 0.96 h) on metal disks than on the skin at 32 degrees C. The method described could be used to assess the survival of other human pathogens on skin and to evaluate the germicidal activity of handwashing agents and other topicals.